INTEGRASI KURIKULUM DEEP LEARNING DALAM PENDIDIKAN: STRATEGI DAN TANTANGAN - Waruwu, David El Roy; Setiawati, Esti (Jurnal Sosialita, 2025)
This research aims to analyze the strategies and challenges in integrating deep learning curriculum in education. Deep learning is applied to improve conceptual understanding, critical thinking skills, and students' readiness to face global challenges. This research uses a literature study method with a descriptive approach, which analyzes various secondary sources, including relevant journals, books, and scientific articles. The results show that the main strategies in deep learning curriculum integration include the project-based learning (PBL) approach, Active Deep Learner eXperience (ADLX), and the utilization of artificial intelligence technology to create a more adaptive and personalized learning experience. In addition, deep learning also emphasizes strengthening character and cultural values in education. However, the implementation of this curriculum faces challenges, such as the readiness of educators, limited infrastructure, difficulties in evaluating learning outcomes, and resistance to change in the education system. Therefore, flexible education policy support, continuous training for educators, and investment in technological infrastructure development are needed to ensure the successful implementation of deep learning in education. Keywords: Strategies, Challenges, Curriculum, and Deep Learning